Leaders in conflict : Bush and Rumsfeld in Iraq - Dyson, Stephen Benedict (Manchester University Press, 2014)
This title shows that George W. Bush and Donald Rumsfeld thought about international politics, and about leadership, in divergent ways, and demonstrates the impact these differences had on the course of the Iraq war.